Jordan : Staff Report for the 2012 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This 2012 Article IV Consultation highlights that the pace of economic activity in Jordan remains subdued. Following a period of robust growth during 2000-09 supported by a favorable external environment, economic activity slowed sharply. Jordan is also facing risks from a further deterioration in its terms of trade and unrest in neighboring countries. Executive Directors have commended the authorities' track record of prudent and effective macroeconomic management. Directors have also welcomed the fiscal tightening in the 2012 budget and the authorities' three-year fiscal reform agenda.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet